Hadith #4917 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
Um Habiba said to Allah’s Messenger (ﷺ) “We have heard that you want to marry Durra bint Abu-Salama.” Allah’s Messenger (ﷺ) said, “Can she be married along with Um Salama (her mother)? Even if I have not married Um Salama, she would not be lawful for me to marry, for her father is my foster brother.”
Grade: Sahih

Hadith #5131 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
When Um Habiba bint Abi Sufyan was informed of her father’s death, she asked for perfume and rubbed it over her arms and said, “I am not in need of perfume, but I have heard the Prophet (ﷺ) saying, “It is not lawful for a lady who believes in Allah and the Last Day to mourn for more than three days except for her husband for whom the (mourning) period is four months and ten days.”
Grade: Sahih

Hadith #5859 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
Um Sulaim said, “O Allah’s Messenger (ﷺ)! Verily Allah is not shy of (telling you) the truth. Is it essential for a woman to take a bath after she had a wet dream (nocturnal sexual discharge)?” He said, “Yes, if she notices discharge. On that Um Salama laughed and said, “Does a woman get a (nocturnal sexual) discharge?” He said, “How then does (her) son resemble her (his mother)?”
Grade: Sahih

Hadith #6795 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
The Prophet (ﷺ) got up from his sleep with a flushed red face and said, “None has the right to be worshipped but Allah. Woe to the Arabs, from the Great evil that is nearly approaching them. Today a gap has been made in the wall of Gog and Magog like this.” (Sufyan illustrated by this forming the number 90 or 100 with his fingers.) It was asked, “Shall we be destroyed though there are righteous people among us?” The Prophet (ﷺ) said, “Yes, if evil increased.”
Grade: Sahih

Hadith #6866 - Sahih al-Bukhari - Zainab bint Salama (Sahih al-Bukhari)
That one day Allah’s Messenger (ﷺ) entered upon her in a state of fear and said, “None has the right to be worshipped but Allah! Woe to the Arabs from the Great evil that has approached (them). Today a hole has been opened in the dam of Gog and Magog like this.” The Prophet (ﷺ) made a circle with his index finger and thumb. Zainab bint Jahsh added: I said, “O Alllah’s Apostle! Shall we be destroyed though there will be righteous people among us?” The Prophet (ﷺ) said, “Yes, i
Grade: Sahih